Europe at [sic] a source of investment for the Caribbean - Hartwich, Dieter (UWI MonaJA, 1994)
Traces the record of the Lome Conventions in the Caribbean. Makes general economic and economic/political comments on the Lome Conventions. Looks at the role which the European Investment Bank is likely to be able to play.